(untitled) (Physical Education, Health and Social Sciences, 2026)
Hepatitis C Virus (HCV) infection is a significant public health problem in Pakistan, being a leading cause in the development of chronic liver disease, cirrhosis, and hepatocellular carcinoma. In resource-constrained districts like Dera Ismail Khan, a key barrier to effective disease management is the lack of affordability of treatments. To assess the clinical outcomes and cost-effectiveness of therapies for the treatment of hepatitis C, the author focuses on the District Dera Ismail Khan, Khyber Pakhtunkhwa, Pakistan, and the use of interferon, pegylated interferon, and ribavirin. A descriptive cross-sectional study was developed based on the physician’s data made through the structured questionnaire. Thirty physicians (30) involved in the management of HCV patients were selected to describe treatment preferences, clinical outcomes, adverse effects, and relative costs of the most commonly prescribed brands of interferon and ribavirin. The response rate was approximately 90%. Uniferon was the most frequently prescribed conventional interferon, accounting for 45%. After Uniferon were Hepaferon (30%), Ceron Alpha (15%), and Roferon (10%). Of the most commonly used brands of ribavirin, Ribazole was prescribed (50%). Physicians indicated that Uniferon and Ribazole were effective, with a lower financial burden, than most alternatives. The combination of Uniferon and Ribazole was the most cost-efficient ribavirin and interferon based regimen for the treatment of HCV in Dera Ismail Khan District. These results show that low-resource areas can successfully implement low-cost treatment plans.